Improvement of operating procedures through the reconfiguration of a plant structure - Hoshino, Satoshi; Seki, Hiroya; Tomoya, Sugimoto; Naka, Yuji (Computer Aided Chemical Engineering, 2008)
In this paper, we aim to improve operating procedures through the reconfiguration of an existing chemical plant structure from the viewpoint of process safety and operability. For this purpose, we first structurize, i.e., decompose and modularize, the correspondence relation between the whole plant structure and the operating procedures with the use of a CGU (Control Group Unit) as the unit. Then, we manage information regarding the order relation of the operations among different CGUs by using a proposed CGU coordination. In this way, it is possible to improve the operating procedures by simply assessing and designing an operation or operating procedure within a CGU that needs to be modified. As an industrial example, we examine a startup procedure for an HDS (hydrodesulfurization) plant.